Profile Analysis of Students’ Concept Understanding on Heat and Temperature - Sukarmin sukarmin; Dewi Ratnasari; Suparmi Suparmi (Journal of Education and Learning (EduLearn), 2018)
This research is aimed to know students’ concept understanding profile on heat and temperature. This research is descriptive research using a qualitative approach. Subjects of this research are 10th-grade students in Surakarta in the academic year of 2016/ 2017. They represent high, medium, and low categorized school. Subject selection is based on the average score of physics at the latest four years. This research uses the question of extended response test through essay question. Before having given to the subjects, essay questions are validated by the experts. Based on the research result and the data analysis, students’ concept understanding on heat and temperature as follows: (1) The average percentage of students’ concept understanding at high categorized school is 60,66%, at medium categorized school is 51,47%, and at low categorized school is 48,83%, (2) Most students have misconception on basic concept of heat and temperature such as heat capacity, thermal conductivity, and expansion concept.